Legal angel: personalized NLP chatbot for legal guidance - Boey, Zhi Xuan (2024)
This project presents a cutting-edge artificial intelligence chatbot created to help with legal inquiries. The chatbot is outfitted with an array of sophisticated functionalities designed to augment user engagement and ease of usage. Voice input, which enables users to interact with the system using natural speech, is one of its main features. This makes the system more intuitive and user-friendly. Furthermore, people with a variety of linguistic backgrounds may easily converse in their favourite languages thanks to the chatbot's capability for multilingual translation. This AI chatbot's ability to learn new things on a constant basis is one of its best qualities. The chatbot may learn new things from users, which enables it to gradually increase and improve its knowledge base. The chatbot's capacity to learn guarantees that it stays current with legal knowledge and can adjust to the changing demands of its users. By adding these functions, the chatbot promotes a more dynamic and customized contact experience while also offering precise and prompt legal aid.